Age-Structured (SVEIHR) Model for Diphtheria Transmission Analysis - Kolawole, mutairu; FADARA, Oladele Ojo; ODEYEMI, kazeem Abidoye (JURNAL DIFERENSIAL, 2025)
The research investigates the transmission dynamics of diphtheria and the role of vaccination asa prominent control measure. A novel Susceptible-Vaccinated-Exposed-Infectious-HospitalizedRecovered (SVEIHR) model is developed to analyze the spread of the disease among age-structuredpopulations. The study focuses on the existence and uniqueness of the disease-free equilibrium andconducts stability analyses of both local and global equilibria. Sensitivity analysis of targeted parameters is performed to evaluate their impact on disease transmission dynamics. Numerical simulationsutilizing the Laplace Adomian Decomposition Method illustrate the effects of these parameters onthe compartments of the model, with results presented graphically. Through this comprehensiveanalysis, the study aims to provide insights into the effectiveness of vaccination strategies in controlling diphtheria and inform evidence-based public health interventions.